2017
DOI: 10.1177/2047487317710803
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cost-effectiveness of home-based cardiac rehabilitation compared to conventional, centre-based cardiac rehabilitation: Results of the FIT@Home study

Abstract: AimAlthough cardiac rehabilitation improves physical fitness after a cardiac event, many eligible patients do not participate in cardiac rehabilitation and the beneficial effects of cardiac rehabilitation are often not maintained over time. Home-based training with telemonitoring guidance could improve participation rates and enhance long-term effectiveness.Methods and resultsWe randomised 90 low-to-moderate cardiac risk patients entering cardiac rehabilitation to three months of either home-based training wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
360
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(387 citation statements)
references
References 53 publications
16
360
2
9
Order By: Relevance
“…Empowering patients to control aspects of their care goes a long way to improving care quality. Research findings support this: compared with patients that do not, patients who participate in medical decisions tend to report more satisfaction with their care [5], enjoy a better quality of life [6], and are adherent to recommendations [7] with greater satisfaction [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Empowering patients to control aspects of their care goes a long way to improving care quality. Research findings support this: compared with patients that do not, patients who participate in medical decisions tend to report more satisfaction with their care [5], enjoy a better quality of life [6], and are adherent to recommendations [7] with greater satisfaction [8]. …”
Section: Introductionmentioning
confidence: 99%
“…The FIT@Home study is a randomized, controlled clinical trial, comparing home-based with centre-based cardiac rehabilitation 7 in ischaemic heart disease patients (N ¼ 90). Home-based patients entered a three-month exercise training programme at home, supervised remotely by heart rate and physical activity telemonitoring.…”
mentioning
confidence: 99%
“…For example, Piotrowicz and colleagues (2015b) found higher exercise capacity and adherence rates in patients with CHF who undertook an eight week home-based telemonitored Nordic walking program, compared with a control group of no exercise. Another study demonstrated that home-based telemonitored exercise results in similar improvements in exercise capacity and health-related quality of life compared with a centre-based exercise in low-to-moderate cardiac risk patients entering cardiac rehabilitation (Kraal et al, 2017).…”
Section: Telerehabilitation Interventionmentioning
confidence: 98%
“…In particular, telerehabilitation is at least as effective as traditional centre-based rehabilitation programs for patients with cardiopulmonary diseases, in terms of exercise capacity as measured by the 6 minute walk test (6MWT) and peak oxygen consumption (Frederix et al, 2015a;Tsai et al, 2017), quality of life (Holland et al, 2016;Piotrowicz et al, 2010), and adverse events (Arthur et al, 2002;Piotrowicz et al, 2015b). Telerehabilitation has higher adherence rates (Piotrowicz et al, 2010;Varnfield et al, 2014), higher patient satisfaction levels and appears to be more cost-effective compared with centre-based programs Kraal et al, 2017). As this is a relatively new research area, there are only a few studies in each disease and the majority used phone-based telerehabilitation.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation